Pursue The Position Of The State Administrative Court In Indonesia - Ahmad Shodiqin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Indonesia is a constitutional state, which means that almost every action taken in it is regulated in accordance with applicable legal provisions. The State Administrative Court is one form of implementing the rule of law. This state administrative court is regulated in Law no. 5 of 1986 concerning the State Administrative Court which is the realization of the provisions of Article 24 of the 1945 Constitution and Article of Law No. 14 of 1970 which was amended by Law no. 35 of 1999 concerning Main Provisions of Judicial Power, whose authority is to inspect to protect and develop and maintain state administration that is right according to law or according to law or right effectively or functions efficiently. Today if we analyze the existing laws in Indonesia socially, there are still many people who are less concerned about the concepts and objectives of the laws issued by the government. Therefore, from this journal, the author intends to provide legal education related to the position of state administrative justice in Indonesia